Examining the effectiveness of the simplified air-cargo express consignment clearance system in Taiwan - Tao Chen (Journal of Shipping and Trade (JST), 2016)
The Simplified Express Consignment Clearance System was first introduced in Taiwan in 2001 to improve the effectiveness and efficiency of customs clearance operations of air cargo. This system, which is based on simplified declaration procedures, is expected to facilitate the effective and efficient collection of taxes and duties even with limited manpower. The Customs Administration (CA) has highlighted the system's efficiency, but its effectiveness is yet to be validated. Thus, this study comprehensively examines this system by adopting both bottom-up and top-down approaches from operation and policy perspectives. Import express cargo clearance records were collected and logistic regression analysis was performed to identify critical factors that influence the system's effectiveness. Results reveal the "inspector" to be the most significant factor. Having a diligent inspector will result in a high number of customs declarations that should be charged for duties or taxes with penalty. This finding questions the notion that the inspector is indeed the most significant factor. Thus, the scope of this study was expanded to cover the simplified system's policy and structure, and concerned parties were interviewed to gain an in-depth understanding. Findings reveal that the system flaw originates from the inability of the simplified system to perform its designated function. This paper offers several contributions to the literature. First, this paper examines the CA's development of the simplified clearance system. Second, this paper provides a detailed analysis of the consignment clearance system's effectiveness and its critical influencing factors. Third, the paper provides new insights into the system flaw and examines the trade-off between the system's efficiency and effectiveness.
Keywords: 650; Simplified express consignment clearance system; Customs administration; Tax evasion; System flaw; Taiwan